Rigid polyurethane foams modified with liginin based bio-polyols - Salach, K. (2017)
Nowadays, a large number of polyurethane (PU) systems modifications relies on the use of different bio-polyols, as described in literature. Among them, one of the most important is the incorporation of bio-polyols based on plant wastes such as lignin. In this work, two bio-polyols have been synthesized from a technical lignin and applied to obtain rigid PU foams (10-30wt. in polyol premix). The lignin, obtained by an organosolv process (aqueous ethanol) proceeds from hardwoods and was converted into liquid bio-polyols by an oxypropylation process. The addition of the lignin-based bio-polyols to the PU system increased its reactivity, as confirmed by a faster decrease of the dielectric polarization and an increase of the maximum temperature in the foam core during the foaming process. The foam modified with these bio-polyols had a slightly lower apparent density and compressive strength. The obtained foams have an apparent density and a closed cell content of about 40 to 45 kg/m3 and 86-89%, respectively. The compressive strength of the foams decrease as the bio-polyol content increased. On the other hand the thermal conductivities of the obtained materials were similar ca. 23 mW/m·K. Concerning thermal stability, lignin-based foams start to degrade at lower temperatures and show a slower degradation pattern (high residue in TG).